Using Positive Behavioral Interventions and Supports to Reduce School Suspensions. (December 2020) - Gage, Nicholas A.; Beahm, Lydia; Kaplan, Rachel; MacSuga-Gage, Ashley S.; Lee, Ahhyun
The Positive Behavioral Interventions and Supports (PBIS) framework is currently implemented in more than 25, 000 schools across the globe. Its implementation has demonstrated positive impacts on a number of behavioral and academic outcomes. A growing evidence base has found that PBIS has been particularly effective at reducing both in- and out-of-school suspensions. This article describes concerns with the use of suspensions, defines PBIS, and outlines how schools can implement and use PBIS to reduce suspensions.